Prenatal diagnosis of Cri-du-Chat syndrome with concomitant distal trisomy 10q syndrome in one fetus with ultrasound anomalies - Jian-Ping He; Yuan Qian; Wei-Jia Liu; Jian Tang; Mao-Hua Qin; Sheng-Jun Luo; Jiang-Hou Hou; Meng-Xin Lv (Elsevier, 2021)
Objective: The aim of this work was to characterize the genetic abnormalities and prenatal diagnosis indications in one fetus with Cri-du-Chat syndrome with codependent 10q24.2-q26.3 duplication in prenatal screening. Materials and methods: A 31-year-old woman had a second trimester serum screening that indicated the fetus was at low risk. During this pregnancy, the woman underwent amniocentesis at 18+4 weeks' gestation because of adverse fertility history and nuchal fold thickening. Cytogenetic analysis and next-generation sequencing analysis were simultaneously performed to provide genetic analysis of fetal amniotic fluid. According to abnormal results, parental chromosome karyotype of peripheral blood was performed to analysis. Results: CNV-seq detected a 14.00 Mb deletion at 5p15.33-p15.2 and a 34.06 Mb duplication at 10q24.2-q26.3 in the fetus. Cytogenetic analysis of the fetus revealed a karyotype of 46, XY, der(5) t(5;10) (p15.2;q26.3). The karyotype of pregnant women was 46,XX,t(5;10) (p15.2;q24.2). The pregnancy was subsequently terminated after sufficient informed consent. Conclusion: This is the first study that reports prenatal diagnosis of a Cri-du-Chat syndrome with concomitant 10 q24.2-q26.3 duplication. Adverse pregnancy history has to be as an important indicator for prenatal diagnosis, and the genetic factors of abnormal pregnancy should be identified before next pregnancy. Nuchal fold thickening is closely related to fetal abnormalities. Combined with ultrasonography, the use of CNV-seq will improve the diagnosis of submicroscopic chromosomal aberrations in fetuses with congenital anomalies.